STRUCTURE AND PROPERTIES OF SOME NATURAL CELLULOSIC FIBRILS - Ramjee Subramanian; Alexy Kononov; Taegeun Kang; Jouni Paltakari; Hannu Paulapuro (BioResources, 2008)
This study examines the properties of cellulosic fibrillar fines manufactured from different pulp raw materials, bleached softwood kraft (bswk), themomechanical (TMP), and non-wood sisal. Chemical characterisation showed that the carbohydrate and lignin contents of sisal were between those of bswk and TMP. Sisal was found to contain about three times more calcium than bswk and TMP. Measurements from the immobilization kinetics showed that the solids content after immobilization was highest for the sisal suspension followed by TMP and bswk. This indicates that the dewatering ability of the fines suspension increases in the order bswk<TMP<sisal. The loss modulus (G'') was maxmium with bswk, indicating that the greatest viscous dissipation before immobilisation took place in the bswk suspension. The strength properties of fines sheets decreased in the order bswk>TMP>sisal. This is due to the highly fibrillated nature of bswk fines, as illustrated by fibre saturation point (FSP), differential scanning calorimetric (DSC), and hydrodynamic specific volume (HSV) measurements.